2012
DOI: 10.4161/auto.21159
|View full text |Cite
|
Sign up to set email alerts
|

Porcine reproductive and respiratory syndrome virus induces autophagy to promote virus replication

Abstract: An increasing number of studies demonstrate that autophagy, an intrinsic mechanism that can degrade cytoplasmic components, is involved in the infection processes of a variety of pathogens. It can be hijacked by various viruses to facilitate their replication. In this study, we found that PRRSV infection significantly increases the number of double- or single-membrane vesicles in the cytoplasm of host cells in ultrastructural analysis. Our results showed the LC3-I was converted into LC3-II after virus infectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
105
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(109 citation statements)
references
References 66 publications
2
105
2
Order By: Relevance
“…The fact that UV-inactivated NDV could not trigger LC3 conversion suggests that viral replication is required to induce autophagy. Previous reports have indicated that some viruses, such as porcine reproductive and respiratory syndrome virus (PRRSV), HCV, and herpes simplex virus, induce an incomplete autophagic response by blocking autophagosome degradation (37)(38)(39). By several means of measuring autophagic flux, including monitoring p62 degradation, LC3-II turnover, and GFP-LC3 lysosomal delivery and proteolysis, we produced strong evidence that autophagic flux was enhanced upon NDV infection.…”
Section: Discussionmentioning
confidence: 77%
“…The fact that UV-inactivated NDV could not trigger LC3 conversion suggests that viral replication is required to induce autophagy. Previous reports have indicated that some viruses, such as porcine reproductive and respiratory syndrome virus (PRRSV), HCV, and herpes simplex virus, induce an incomplete autophagic response by blocking autophagosome degradation (37)(38)(39). By several means of measuring autophagic flux, including monitoring p62 degradation, LC3-II turnover, and GFP-LC3 lysosomal delivery and proteolysis, we produced strong evidence that autophagic flux was enhanced upon NDV infection.…”
Section: Discussionmentioning
confidence: 77%
“…Thus, many pathogens, including viruses, have developed strategies for self-protection and further manipulate or utilize autophagy to their own advantages. For example, Epstein-Barr virus (EBV) and Kaposi's Sarcoma-Associated Herpes Virus (KSHV) negatively regulate autophagy during latency, whereas poliovirus (18,19), porcine reproductive and respiratory syndrome virus (PRRSV) (20), encephalomyocarditis virus (21), and picornavirus (22), utilize components of the autophagy pathway to promote viral replication. Some of the viruses use the autophagosome as a membrane structure to support its replication as well as to hijack it as a mechanism for releasing the packaged virions in a non-lytic manner.…”
Section: The Autophagy Induced By Hbv Leads Autophagic Degradationmentioning
confidence: 99%
“…This promotes the fusion of the autophagosome with the plasma membrane (12,19,21,23,24). While viruses promote autophagy induction, it has been shown that they have developed mechanisms to inhibit the maturation of autophagosomes by preventing the fusion between the autophagosome and the lysosome (19,20). However, recent findings also indicate that some RNA viruses benefit from autophagosome maturation.…”
Section: The Autophagy Induced By Hbv Leads Autophagic Degradationmentioning
confidence: 99%
“…Autophagy also contributes to innate and adaptive immunity against a wide variety of intracellular microbial pathogens, including bacteria, viruses and protozoa [14,15]. An increasing amount of evidences suggest that the autophagy processes are also exploited by many viruses for their replication, such as the measles virus (MeV) [16], PPRV [17], hepatitis C virus [18], classical swine fever virus (CSFV) [19], porcine reproductive and respiratory syndrome virus (PRRSV) [20], avian reovirus [21], and influenza A virus [22]. However, it has been demonstrated that autophagy is involved in the elimination of the herpes simplex virus [23], foot-and-mouth disease virus [24], human rotavirus [25] and cytomegalovirus [26].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, there are a variety of mechanisms by which the apoptotic and autophagic pathways are intertwined to affect cell fate [30]. It has been demonstrated that viruses can exploit autophagy and apoptosis for their replication [20,31,32]. A previous study suggested that autophagy can promote PRRSV replication by postponing apoptosis through the formation of a Bad-Beclin-1 complex [33].…”
Section: Introductionmentioning
confidence: 99%